Effects of Berries Consumption on Cardiovascular Risk Factors: A Meta-analysis with Trial Sequential Analysis of Randomized Controlled Trials - Huang, Haohai; Chen, Guangzhao; Liao, Dan; Zhu, Yongkun; Xue, Xiaoyan (Scientific reports, 2016)
The effects of berries consumption on cardiovascular disease (CVD) risk factors have not been systematically examined. Here, we aimed to conduct a meta-analysis with trial sequential analysis to estimate the effect of berries consumption on CVD risk factors. PubMed, Embase and CENTRAL were searched for randomized controlled trials (RCTs) that regarding the effects of berries consumption in either healthy participants or patients with CVD. Twenty-two eligible RCTs representing 1,251 subjects were enrolled. The pooled result showed that berries consumption significantly lowered the low density lipoprotein (LDL)-cholesterol [weighted mean difference (WMD), −0.21 mmol/L; 95% confidence interval (CI), −0.34 to −0.07; P = 0.003], systolic blood pressure (SBP) (WMD, −2.72 mmHg; 95% CI, −5.32 to −0.12; P = 0.04), fasting glucose (WMD, −0.10 mmol/L; 95% CI, −0.17 to −0.03; P = 0.004), body mass index (BMI) (WMD, −0.36 kg/m 2 ; 95% CI, −0.54 to −0.18, P < 0.00001), Hemoglobin A1c (HbA1c) (WMD, −0.20%; 95% CI, −0.39 to −0.01; P = 0.04) and tumor necrosis factor-α (TNF-α) (WMD, −0.99 ρg/mL; 95% CI, −1.96 to −0.02; P = 0.04). However, no significant changes were seen in other markers. The current evidence suggests that berries consumption might be utilized as a possible new effective and safe supplementary option to better prevent and control CVD in humans.